General Techniques of Cell Culture - Harrison, Maureen A.; Rae, Ian F. (Handbooks in practical animal cell biology, 1997)
Cell culture techniques are invaluable to the modern researcher but difficult to carry out successfully. As part of the series of Handbooks in Practical Animal Cell Biology, this volume offers a concise practical guide to the basic essentials of the technique. Researchers new to cell culture will find a clear explanation of the essential equipment of a tissue culture facility, including tissue culture media and sera. It describes methods for growing suspension and adhesion cultures, including how to store cells and prepare primary cultures from cells. For those already culturing cells , the handbook will act as a handy reference to the basic techniques. The essence of the book is to deal with the generalities of cell culture and to give a grasp of the basic concepts before involvement in more specialized work in the field. Ideal for anyone moving into tissue cell culture techniques or looking for a concise reference book.